2023
DOI: 10.1021/acs.langmuir.3c00634
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Observation of Long-Lasting and Self-Sustaining Marangoni Flow

Abstract: When solute molecules in a liquid evaporate at the surface, concentration gradients can lead to surface tension gradients and provoke fluid convection at the interface, a phenomenon commonly known as the Marangoni effect. Here, we demonstrate that minute quantities of ethanol in concentrated sodium hydroxide solution can induce pronounced and long-lasting Marangoni flow upon evaporation at room temperature. By employing particle image velocimetry and gravimetric analysis, we show that the mean interfacial spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In fact, using a video microscope, we observed that the carbon particles in the aqueous ethanol solution droplet moved sufficiently fast against the measurement interval, which is a phenomenon commonly known as Marangoni flow. 37,38) The developed method can obtain the physical properties of a droplet with high time resolution and capture unsteady phenomena, as shown in Fig. 7.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, using a video microscope, we observed that the carbon particles in the aqueous ethanol solution droplet moved sufficiently fast against the measurement interval, which is a phenomenon commonly known as Marangoni flow. 37,38) The developed method can obtain the physical properties of a droplet with high time resolution and capture unsteady phenomena, as shown in Fig. 7.…”
Section: Resultsmentioning
confidence: 99%
“…For verification of these models, the Marangoni number ( Ma - a dimensionless number that characterizes the Marangoni effect) can be used M a = Δ σ L m μ D Here, Δσ is the change in the interfacial tension [MT –2 ] (due to a solute concentration) along the characteristic length L m ; μ is the dynamic viscosity [ML –1 T –1 ]; and D is the diffusion coefficient [L 2 T –1 ] . The Marangoni number concept is applicable to studies across scales , and thus adaptable to quantitative studies of the PFAS interaction in multiphase systems for the development of transport model systems.…”
Section: Upscaling From Molecular Scale Behaviormentioning
confidence: 99%
“…The Soret effect, or thermal diffusion, causes a separation of the mixture components in response to a temperature gradient. , The Marangoni effect, on the other hand, induces fluid motion along the interface due to a surface tension gradient. This effect can cause the vapor bubbles in the binary mixture to shift toward the high-temperature area, further promoting liquid replenishment at the nucleation sites and preventing dry-out. , The impact of the Soret and Marangoni effects on heat transfer characteristics has been well-documented for plain surfaces. However, there is a lack of theoretical frameworks and empirical correlations that account for the influence of heater surface attributes on these complex phenomena.…”
Section: Introductionmentioning
confidence: 99%